Author Correction: Substantiating freedom from parasitic infection by combining transmission model predictions with disease surveys. Issue 1 (December 2018) - Michael, Edwin; Smith, Morgan; Katabarwa, Moses; Byamukama, Edson; Griswold, Emily; Habomugisha, Peace; Lakwo, Thomson; Tukahebwa, Edridah; Miri, Emmanuel; Eigege, Abel; Ngige, Evelyn; Unnasch, Thomas; et al.
The original version of this Article contained an error in the spelling of Emily Griswold, which was incorrectly given as Emily Grisworld. This error has now been corrected in both the PDF and HTML versions of the Article.